2015
DOI: 10.1021/es505728f
|View full text |Cite
|
Sign up to set email alerts
|

Nonaqueous System of Iron-Based Ionic Liquid and DMF for the Oxidation of Hydrogen Sulfide and Regeneration by Electrolysis

Abstract: To improve the hydrogen sulfide removal efficiency with the application of an iron-based imidazolium chloride ionic liquid (Fe(III)-IL) as desulfurizer, Fe(II) and N,N-dimethylformamide (DMF) are introduced to Fe(III)-IL to construct a new nonaqueous desulfurization system (Fe(III/II)-IL/DMF). Following desulfurization, the system can be regenerated using the controlled-potential electrolysis method. The addition of Fe(II) in Fe(III)-IL is beneficial for the hydrogen sulfide removal and the electrochemical reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…The attachment or solubility of the DBT molecules into the co‐solvent hexane can be identified by observing the new peak in the Raman spectra (Figure ) within the range of 1,600 cm. The results are in good agreement with the reported studies …”
Section: Resultssupporting
confidence: 93%
“…The attachment or solubility of the DBT molecules into the co‐solvent hexane can be identified by observing the new peak in the Raman spectra (Figure ) within the range of 1,600 cm. The results are in good agreement with the reported studies …”
Section: Resultssupporting
confidence: 93%
“…However, Lee et al stated that [Bmim]­FeCl 4 was partially soluble in water at room temperature, due to the hydrogen bonding interactions between FeCl 4 – and water molecules and the hydrophilic imidazolium ring. Moreover, the solvent effect will greatly decrease the stability of Fe–Cl bonds in FeCl 4 – anions, which may lead to the decomposition of FeCl 4 – anions, owing to the relatively weak interaction of Fe–Cl bonds (2.225 Å) compared to Fe–N bonds (2.065 Å) . By regulating the ligand species, the novel metal complex ILs containing more stable iron complex ions such as biomimetic [(Porp)­Fe­(III)] + that can activate oxygen and basic [Fe­(EDTA)] − have been prepared. Unlike metal chloride ILs and POM-ILs, the metal complex ions can be incorporated in cations and/or anions in the metal complex ILs with different ligands, which results in various types of metal complex ILs with particular properties (Tables S1–S3).…”
Section: Identification and Physicochemical Properties Of Milsmentioning
confidence: 99%
“…Nonaqueous wet oxidation desulfurization process and desulfurization mechanism: (a) Nonaqueous wet oxidation desulfurization process in Fe-IL and the Fe-IL regenerated by air. (b) ODS mechanism of H 2 S removal in Fe­(III/II)-IL/DMF system …”
Section: Oxidative Desulfurization Of H2s In Milsmentioning
confidence: 99%
“…Many studies have reported the potential use and candidacies of conventional room temperature ILs (RTILs) for H 2 S conversion experimentally [10,11]. However, it is found out that the solubility and capacity of H 2 S in these ILs are still low at low pressure and thus, unable to perform their tasks efficiently [12][13][14][15][16]. Therefore, a new kind of ILs, Task Specific ILs (TSILs) such as metal chloride anion based ILs has been proposed in this research for conversion of H 2 S [17,18].…”
Section: Introductionmentioning
confidence: 99%